2005
DOI: 10.1038/ni1244
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between conventional dendritic cells and natural killer cells is integral to the activation of effective antiviral immunity

Abstract: Dendritic cells (DCs) regulate various aspects of innate immunity, including natural killer (NK) cell function. Here we define the mechanisms involved in DC-NK cell interactions during viral infection. NK cells were efficiently activated by murine cytomegalovirus (MCMV)-infected CD11b(+) DCs. NK cell cytotoxicity required interferon-alpha and interactions between the NKG2D activating receptor and NKG2D ligand, whereas the production of interferon-gamma by NK cells relied mainly on DC-derived interleukin 18. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
251
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(267 citation statements)
references
References 56 publications
13
251
2
1
Order By: Relevance
“…Where the two models appear to differ is in the role of NKG2D. Whereas, we find that NKG2D is essential for enhanced IFN-␥ production by human NK cells responding to influenza, Andoniou et al (52) find no contribution of NKG2D in enhancing IFN-␥ by mouse NK cells responding to murine CMV. This distinction could be due to evolved differences in the human and mouse immune systems (79), or between influenza and murine CMV, two divergent viruses with unrelated structure, genetics, and pathogenesis (80 -82).…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Where the two models appear to differ is in the role of NKG2D. Whereas, we find that NKG2D is essential for enhanced IFN-␥ production by human NK cells responding to influenza, Andoniou et al (52) find no contribution of NKG2D in enhancing IFN-␥ by mouse NK cells responding to murine CMV. This distinction could be due to evolved differences in the human and mouse immune systems (79), or between influenza and murine CMV, two divergent viruses with unrelated structure, genetics, and pathogenesis (80 -82).…”
Section: Discussioncontrasting
confidence: 76%
“…Our study shows that NK cell activation requires several cues mediated by cell surface and secreted factors, including the recognition by NKG2D and NKp46 of influenzainduced ligands on the infected DCs. Although previously identified as mediators of NK cell killing (35,43,51,52), the NKG2D and NKp46 receptors are now shown to have a more constructive role as seen here in the activation of NK cells by influenza-infected DCs.…”
Section: Nkp46 and Nkg2d Recognition Of Infected Dendritic Cells Is Nmentioning
confidence: 50%
See 1 more Smart Citation
“…Notably, the ligand on MCA-transformed cells undergoes immune editing by NKp46/NCR1 pressure (14), whereas the ligand on D122 cells described in this study apparently does not. Finally, we have recently shown that a ligand for NKp46/NCR1 is expressed by human and mouse b cells (27,28), and it was also demonstrated that upon human CMV infection of dendritic cells, an unknown ligand of NKp46/NCR1 is downregulated to prevent NK cell-mediated lysis of the infected dendritic cells (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are therefore consistent with the observations of Kamath et al (21) who showed that T cell activation is likely a common response to infection and can be mediated by the triggering of several different TLRs. DCs are known to interact with CD4 ϩ T cells and recent reports have shown the importance of DC-NK cell interactions in modulating immune responses (5,6,22). Interestingly, when conventional DCs were depleted from transgenic mice, only TLR4 and TLR5 agonists failed to induce significant immune cell recruitment to the draining lymph nodes, showing similarities in DC signaling through TLR4 and TLR5.…”
Section: Discussionmentioning
confidence: 98%